Letter - Winstanley, E.
029-0073-001 Telegraphic address: "Wholesale Manchester" Telephone: Blackfriars 1212 Extension No. Please address your reply: Co-operative Wholesale Society Limited, Exporters, Buying and Shipping Agents, 1, Balloon Street, Manchester, 4. Cable Codes: A.B.C., 6th and 7th editions; Western Union 5 letter; Bentley Complete Phrase; Bentley Second Phrase; A.1. MARCONI, and Private. Our reference EXPORT ST/HP. 345 Your reference 20th December, 1937. The Trades union Congress General Council, Transport House, Smith Square, LONDON. Dear Sirs, We beg to make further reference to correspondence exchanged between us relative to your order of the 9th instant, in respect of Corned Beef, Bacon etc. for shipment by s.s. HARTBRIDGE to Barcelona. You will recollect that the s.s. HARTBRIDGE was originally scheduled to sail from Newcastle about the 15th instant, and it was on this basis that we quoted you the insurance rate of £5. 5. 0.%, including war risks. Unfortunately, the vessel in question has still not sailed and consequently the underwriters are demanding a higher premium and quote the figure of £10. 5. 0.% for early shipment. In view of this development, we shall be glad of your instructions regarding insurance by return. At the same time, we should like to point out that we have been in constant communication with the Mid-Atlantic Shipping Co. who have chartered this vessel on behalf of the Spanish Government, and we regret to state that a further difficulty has arisen inasmuch as the owner of the vessel has now declared his unwillingness to sail for Barcelona. This matter is in dispute and immediately we have any final information we will communicate with you further. Meanwhile, we remain, Yours faithfully, E. Winstanley Export Department. 292/946/29/73